Endophytic Bacillus spp. from medicinal plants inhibit mycelial growth of Sclerotinia sclerotiorum and promote plant growth - Ansary, Most. Waheda Rahman; Prince, M.A. Ferdous Rezwan Khan; Haque, Effi; Sultana, Farzana; West, Helen M.; Rahman, Md. Mahbubur; Mondol, Mojid; Akanda, Abdul Mannan; Rahman, Mahfuz; Clarke, Michele L.; Islam, Md. Tofazzal (De Gruyter, 2018)
Plant growth promoting bacteria that are also capable of suppressing plant pathogenic fungi play an important role in sustainable agriculture. There is a critical need of conducting research to discover, characterize and evaluate efficacy of new strains of such bacteria in controlling highly aggressive plant pathogens. In this study, we isolated endophytic bacteria from medicinal plants of Bangladesh and evaluated their antagonistic capacity against an important phytopathogenic fungus Sclerotinia sclerotiorum. Growth promoting effects of those isolates on cucumber and rice seedlings also were assessed. Among 16 morphologically distinct isolates, BDR-2, BRtL-2, and BCL-1 significantly inhibited the growth of S. sclerotiorum through induction of characteristic morphological alterations in hyphae and reduction of mycelial dry weight. When cucumber and rice seeds were treated with these endophytic bacteria, seven isolates (BCL-1, BDL-1, BRtL-2, BRtL-3, BDR-1, BDR-2 and BBoS-1) enhanced seed germination, seedling vigor, seedling growth, and number of roots per plant at varying level compared to untreated controls. All isolates produced high levels of indole-3-acetic acid (6.3 to 63μg mL−1) in vitro. Two most potential isolates, BDR-2 and BRtL-2 were identified 34 as Bacillus amyloliquefaciens and B. subtilis, respectively based on the 16S rRNA gene sequencing. These results suggest that endophytic Bacillus species from native medicinal plants have great potential for using as natural plant growth promoter and biopesticides in sustainable crop production.